2001
DOI: 10.4049/jimmunol.167.5.2895
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of CD18 Integrins in Mediating Lung Neutrophil Sequestration and Increased Microvascular Permeability Induced byEscherichia coliin Mice

Abstract: The in vivo contributions of CD18 integrin-dependent and -independent mechanisms in mediating the increases in lung neutrophil (polymorphonuclear leukocyte; PMN) sequestration and microvascular permeability are not well understood. We determined the time course of these responses to Gram-negative sepsis in the mouse lung and addressed the specific contributions of CD18 integrins and ICAM-1. PMN sequestration in the lung was assessed by morphometric analysis, and transalveolar PMN migration was assessed by bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 37 publications
(48 reference statements)
4
77
0
Order By: Relevance
“…Firm adhesion and transmigration is predominantly dependent on  2 -integrins on PMN interaction with their counterreceptors, believed to be predominantly ICAM-1 (8)(9)(10). Mice receiving anti-CD11b antibody and/or anti-ICAM-1 antibody demonstrated a dramatic reduction in pulmonary neutrophils recruitment compared with control mice (24). In the present study, we observed a significant increase in the expression of selectins, ICAM-1 and CD11b in C3H and B6 mice following infection with Cm on day 7 postinfection.…”
Section: Discussionsupporting
confidence: 59%
“…Firm adhesion and transmigration is predominantly dependent on  2 -integrins on PMN interaction with their counterreceptors, believed to be predominantly ICAM-1 (8)(9)(10). Mice receiving anti-CD11b antibody and/or anti-ICAM-1 antibody demonstrated a dramatic reduction in pulmonary neutrophils recruitment compared with control mice (24). In the present study, we observed a significant increase in the expression of selectins, ICAM-1 and CD11b in C3H and B6 mice following infection with Cm on day 7 postinfection.…”
Section: Discussionsupporting
confidence: 59%
“…Purity of PMN preparations as assessed by examination of HEMA3 (Fisher)-stained cytospin (Shandon, Pittsburgh, PA) preparations (27) was ϳ90 -95% and viability assessed by Trypan blue exclusion was Ͼ95%.…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary Microvascular Permeability and Edema Formation-K f,c was measured to determine pulmonary microvascular permeability to liquid and the rate of edema formation was continuously monitored by determining lung wet weight changes as described (25,27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations